Supply of sanitary wares, fixtures and fittings with all necessary accessories for 13 storied Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212 - Brac University (Brac University, 2023)
This agreement made between Brac University and Tilottoma Gulshan. to supply of sanitary wares, fixtures and fittings with all necessary accessories for 13 storied Brac University new campus project